Legal Protection for Pharmacists in Performing Pharmaceutical Work, Specifically the Management of Narcotic, Psychotropic, and Precursor Drugs in Healthcare Facilities - Rifai, Ibnu Shina; Prastopo, Prastopo (JURNAL HUKUM SEHASEN, 2025)
The management of narcotics, psychotropics, and precursor drugs in healthcare facilities is a highly sensitive area prone to abuse. Pharmacists, as healthcare professionals responsible for managing these medications, play a crucial role in ensuring the availability, safety, and appropriate use of drugs for patients. However, in carrying out their duties, pharmacists often face various ethical and legal dilemmas and challenges. On the one hand, pharmacists must ensure that patients receive the right medication according to their medical needs. On the other hand, they must also comply with applicable laws and regulations, which are stringent and complex, regarding the handling of narcotics, psychotropics, and precursors. In some cases, pharmacists may even become entangled in legal issues due to actions taken in the course of their professional duties. Therefore, legal protection for pharmacists in performing pharmaceutical work, especially in managing drugs containing narcotics, psychotropics, and precursors, is crucial. With adequate legal protection, pharmacists can carry out their professional duties more professionally, responsibly, and without fear of legal repercussions. Ultimately, this will positively impact the improvement of healthcare quality for the public